2016
DOI: 10.1038/srep33637
|View full text |Cite
|
Sign up to set email alerts
|

Textile Organic Electrochemical Transistors as a Platform for Wearable Biosensors

Abstract: The development of wearable chemical sensors is receiving a great deal of attention in view of non-invasive and continuous monitoring of physiological parameters in healthcare applications. This paper describes the development of a fully textile, wearable chemical sensor based on an organic electrochemical transistor (OECT) entirely made of conductive polymer (PEDOT:PSS). The active polymer patterns are deposited into the fabric by screen printing processes, thus allowing the device to actually “disappear” int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
125
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(133 citation statements)
references
References 40 publications
1
125
0
Order By: Relevance
“…Within this context, OECTs-based sensors seem particularly suitable for the fabrication of wearable devices, essentially for three main reasons [60]. First, as described in earlier sections, OECTs are biased using very low voltages (<1 V), allowing the utilization of portable, low-power sources.…”
Section: Oects For Wearable Electronics Applicationsmentioning
confidence: 99%
“…Within this context, OECTs-based sensors seem particularly suitable for the fabrication of wearable devices, essentially for three main reasons [60]. First, as described in earlier sections, OECTs are biased using very low voltages (<1 V), allowing the utilization of portable, low-power sources.…”
Section: Oects For Wearable Electronics Applicationsmentioning
confidence: 99%
“…Caldara et al [109] reported the efficient monitoring of sweat pH by a wearable sensor based on a cotton fabric treated with an organically modified silicate and miniaturized and low-power electronics with wireless interfaces. In a separate study, a fully textile, wearable organic electrochemical transistor (OECT) sensor for the detection of biomarkers in external body fluids was developed by Gualandi et al without using an invasive electrode [110].…”
Section: Textiles In Advanced Health Carementioning
confidence: 99%
“…Organic‐based FET (OFET) biosensing devices have gathered a lot of attention as they typically engage large‐area processable semiconductors (SCs) as channel materials; so, they can be, in principle, produced at low cost. Moreover, organic semiconductors can be biocompatible and so amenable to be used for implantable bioelectronic systems.…”
Section: Introductionmentioning
confidence: 99%